METHODOLOGY OF COMPLEX MONITORING RESEARCH OF INNOVATIVE ACTIVITY OF EDUCATIONAL ORGANIZATIONS IN THE REGIONS OF RUSSIAN FEDERATION - O. Kabanova; J. Dyakova (Вестник Северо-Кавказского федерального университета)
The article presents the development of a comprehensive methodology for monitoring innovative activities of educational organization in the regions of Russian Federation. To achieve the stated goal, the indicators of innovative activity of educational organizations were identified, which allow to assess the level of their innovative activity. The complex integral indicator of innovative activity of educational organizations was offered and its criterion values were proved. The development of a methodology for monitoring innovative activity of educational institutions will allow to create a system for monitoring innovative activity and level of innovative activity educational organizations with further implementation in the form of a software product.